2021
DOI: 10.1186/s12909-021-02576-0
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to volunteer and readiness to practice of undergraduate medical students during the COVID-19 pandemic: a cross-sectional survey in Indonesia

Abstract: Background The question to involve or restrict medical students’ involvement in the coronavirus disease 2019 (COVID-19) pandemic response remains contentious. As their state of preparation and perceptions in volunteering during this pandemic have yet to be investigated, this study aims to evaluate Indonesian medical students’ willingness to volunteer and readiness to practice during the COVID-19 pandemic. Methods A web-based survey was conducted am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
109
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(139 citation statements)
references
References 33 publications
15
109
3
1
Order By: Relevance
“…Our study participants acknowledged that the monetary remuneration enticed them to volunteer and sustained their volunteering efforts. This differed from Lazarus et al’s study [ 10 ], which reported a lack of association between monetary incentives and increased willingness to volunteer among undergraduate medical students in Indonesia. Additionally, our student participants suggested including volunteering as part of their clinical placement hours to incentivize peers to volunteer.…”
Section: Discussioncontrasting
confidence: 97%
See 3 more Smart Citations
“…Our study participants acknowledged that the monetary remuneration enticed them to volunteer and sustained their volunteering efforts. This differed from Lazarus et al’s study [ 10 ], which reported a lack of association between monetary incentives and increased willingness to volunteer among undergraduate medical students in Indonesia. Additionally, our student participants suggested including volunteering as part of their clinical placement hours to incentivize peers to volunteer.…”
Section: Discussioncontrasting
confidence: 97%
“…Our findings highlighted the strong collectivist Asian family values and culture that Singapore students hold, regarding placing their family first. Similar findings on the fears for their family’s health were reported among medical students in Indonesia [ 10 ]. Family interests are expected to overrule those of the individual [ 21 ].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…While several studies have shown that some students whether in the medical and dental field are willing to volunteer and put in extra hours to make up for this deficit ( 3 ), there is lack of infrastructural and protocol-based support to facilitate the same. Furthermore, till the time vaccination targets are achieved to allow for the existence of herd immunity, there may be poor response from the patient’s side as well.…”
mentioning
confidence: 99%